Political information-seeking and political efficacy : applying the uses and gratifications theory - Ahmed, Ismail Sheikh Yusuf (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Political information seeking, a popular concept in the field of mass communication, examines why people seek information on politics from traditional and new media. People seek information on politics for different motives. The current study explores the determinants of political information seeking among the Malaysian voters from the Uses and Gratifications perspective. The study employs the survey method to collect data from 2030 respondents who were selected by quota sampling from two parliamentary constituencies in each state. The study was conducted in July 2012 and data were analyzed using SPSS for both descriptive and inferential statistics to answer the research objectives and hypotheses. The study found two motives for political information seeking: vote guidance and diversion. These motives were significantly correlated with political efficacy, interpersonal discussions on politics, and media exposure. Moreover, the study found significant differences among demographics with regard to media exposure and internet use. These differences were mainly related to age, education and family. Implications of the study, future research scope and recommendations were further elaborated.